2018
DOI: 10.1161/jaha.118.008819
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Change in Total Cholesterol Levels on Cardiovascular Disease Among Young Adults

Abstract: BackgroundAlthough high serum cholesterol in young adults is known to be a predictor for cardiovascular events, there is not enough evidence for the association of cholesterol level change with cardiovascular disease (CVD). This study aimed to evaluate whether the change in cholesterol is associated with incidence of CVD among young adults.Methods and ResultsWe examined 2 682 045 young adults (aged 20–39 years) who had undergone 2 consecutive national health check‐ups provided by Korean National Health Insuran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 42 publications
4
73
1
1
Order By: Relevance
“…However, the study by Zhang only had access to laboratory results and did not have access to past medical history and physical examination, which may not be generalizable to healthy populations or those with low cardiovascular risks. Our suggested cut off point of 210 is line with other previous studies [25, 26] that showed TC cutoff range from 200 to 210 mg/dL was appropriate for early intervention while the TC cutoff point of 230 to identify those at high risk is also supported by the literature in a large population study with 10-year follow up [27, 28]. These studies demonstrated that a higher risk of ischemic heart disease was found in the high cholesterol group with a TC level ≥ 240 mg/dL.…”
Section: Discussionsupporting
confidence: 89%
“…However, the study by Zhang only had access to laboratory results and did not have access to past medical history and physical examination, which may not be generalizable to healthy populations or those with low cardiovascular risks. Our suggested cut off point of 210 is line with other previous studies [25, 26] that showed TC cutoff range from 200 to 210 mg/dL was appropriate for early intervention while the TC cutoff point of 230 to identify those at high risk is also supported by the literature in a large population study with 10-year follow up [27, 28]. These studies demonstrated that a higher risk of ischemic heart disease was found in the high cholesterol group with a TC level ≥ 240 mg/dL.…”
Section: Discussionsupporting
confidence: 89%
“…9 Dyslipidemia is known as the main cause of CVD, and the first-line goal in reducing CVD-related morbidity is to lower LDL-C. 15 However, several studies have indicated that elevated levels of not only LDL-C but also other blood lipids (TC, TG, and VLDL) are risk factors for CVD, and that controlling these lipid levels will further reduce CVD-related morbidity. 4,17,18 In the present study, reductions from baseline in TC, TG, and VLDL-C levels at weeks 4 and 8 were significantly greater with the pitavastatin/fenofibrate combination therapy compared to those with pitavastatin monotherapy. In particular, TG and VLDL-C levels at weeks 4 and 8 were significantly reduced compared to the baseline levels.…”
Section: Discussionsupporting
confidence: 46%
“…In addition, this study did not consider that the goals and treatment methods associated with dyslipidaemia differ according to levels of cardiovascular risks. However, in a recent study [16] of young adults aged 20 to 39 years in Korea, the risks of ischaemic heart disease and cerebrovascular disease were reduced if total cholesterol levels were reduced to a lower class than was observed in the previous examination, when dividing total cholesterol levels into the following categories: low (< 180 mg/dL), middle (180-240 mg/dL), high (≥ 240 mg/dL). Therefore, it is meaningful to compare the degree of change in cholesterol levels alone, as was done in the current study.…”
Section: Discussionmentioning
confidence: 69%